Big Data – Concepts, Applications, Challenges and Future Scope - SINGHA, ANJANI KUMAR (IJRDO -Journal of Computer Science Engineering, 2017)
The term, Big Data‘ has been coined to refer to the gargantuan bulk of data that cannot be dealt with by traditional data-handling techniques. Big Data is still a novel concept, and in the following literature we intend to elaborate it in a palpable fashion. It commences with the concept of the subject in itself along with its properties and the two general approaches of dealing with it. The comprehensive study further goes on to elucidate the applications of Big Data in all diverse aspects of economy and being. The utilization of Big Data Analytics after integrating it with digital capabilities to secure business growth and its visualization to make it comprehensible to the technically apprenticed business analyzers has been discussed in depth. Aside this, the incorporation of Big Data in order to improve population health, for the betterment of finance, telecom industry, food industry and for fraud detection and sentiment analysis have been delineated. The challenges that are hindering the growth of Big Data Analytics are accounted for in depth in the paper. This topic has been segregated into two arenasone being the practical challenges faces whilst the other being the theoretical challenges. The hurdles of securing the data and democratizing it have been elaborated amongst several others such as inability in finding sound data professionals in required amounts and software that possess ability to process data at a high velocity. Through the article, the authors intend to decipher the notions in an intelligible manner embodying in text several use-cases and illustrations